Compensation on Preventive Discipline: Mediating the role of Employee Engagement - Dudung Juhana (Kontigensi : Jurnal Ilmiah Manajemen, 2019)
Previous research shows that compensation has a positive effect on employee empowerment and discipline. In this study, the authors conducted a more specific study of the impact of indirect compensation on employee discipline that is preventive mediated by employee empowerment. This research is a survey of bank employees at one bank in Bandung with 30 random employees simple random sampling technique. Hypothesis testing using PLS-SEM. The results showed that there was a significant effect of indirect compensation on employee empowerment and preventive discipline. The research implications indicate that indirect compensation can increase employee empowerment and preventive discipline.